The role of education in the intersection of partnership transitions and motherhood in Europe and the United States - Julia Mikolai; Ann Berrington; Brienna Perelli-Harris (Demographic Research, 2018)
Background: Previous research has shown that partnership status at first birth is associated with education across Europe and the United States. Most research has indicated that first births within cohabitation have a negative educational gradient. However, the pathway to a first birth in different partnership types can be complex and may vary across countries. Objective: We study whether any educational differences observed at the time of a first birth are produced upon entrance into cohabitation, during the transition from cohabitation to marriage, or during the transition to first birth. Methods: Using data from the Harmonized Histories we estimate multi-state event history models to examine how educational differences in patterns of early family formation emerge among women born between 1950 and 1969 in 16 European countries and the United States. Results: The results highlight three main findings. First, the educational gradient of entry into cohabitation is inconsistent across countries. Second, regardless of the educational gradient of entry into cohabitation, the transition to a first birth among cohabiting women has a consistent negative educational gradient across countries. Last, the transition from cohabitation to marriage has a consistent positive educational gradient across countries. Contribution: Across Europe and the United States, educational differences matter the most during the transition from cohabitation to marriage and the transition to first birth once women are in a cohabiting union. Entrance into cohabitation is common, but key educational distinctions emerge upon childbearing. Disadvantaged women are less likely to marry before having a baby, while highly educated women marry before childbearing.